Determination of furosemide levels in pharmaceutical preparations - İbrahim Pirinçci; İzzet Karahan; Kadir Servi; Haki Kara (Eurasian Journal of Veterinary Sciences)
Furosemide is an orthochtorosuHonamid derivative that is a potent diuretic. This compound marketed by some chemical factories is an agent widely used tor therapy of oedema. This study was made to investigate whether preparations had the description levels of furosemide or not. Furosemide preparations were analyzed by spectrophotometry method. Absorbances were measured at 630 nm. Means of turosemide levels in the tablets and solutions were determinated 39.96±1.89 and 18.62±0.64 mg respectively.